2022
DOI: 10.3390/foods11142004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Quality Attributes of Selected Long-Life Food at Four Different Temperatures over Prolonged Storage

Abstract: This study reports the development of selected indicators affecting changes in food quality and safety of selected long-life canned (Szeged goulash, canned chicken meat, pork pâté, canned tuna fish) and dehydrated (instant goulash soup) food during a two-year storage experiment at four different temperatures. The storage temperatures were selected to represent Arctic (−18 °C), temperate (5 °C), subtropical (25 °C) and tropical (40 °C) climatic zones where such food is likely to be stored during, for example, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The pH values were not affected by the fat content (p ≥ 0.05), which is consistent with the work of Lorenzo et al [1], Lorenzo and Pateiro [9], and Estévez et al [34], who found no significant differences in pH in foal pâtés with various fat contents. Ammonia is considered an intermediate or final product of the reactions of nitrogenous compounds released during the course of the Maillard reaction complex and Strecker degradation of amino acids [17,36]. Consistent with this statement, an increase in ammonia amount of 22 and 32% was observed as a result of the sterilisation process in P30 and P40, respectively (p < 0.05; Table 2).…”
Section: Chemical Analysissupporting
confidence: 62%
See 2 more Smart Citations
“…The pH values were not affected by the fat content (p ≥ 0.05), which is consistent with the work of Lorenzo et al [1], Lorenzo and Pateiro [9], and Estévez et al [34], who found no significant differences in pH in foal pâtés with various fat contents. Ammonia is considered an intermediate or final product of the reactions of nitrogenous compounds released during the course of the Maillard reaction complex and Strecker degradation of amino acids [17,36]. Consistent with this statement, an increase in ammonia amount of 22 and 32% was observed as a result of the sterilisation process in P30 and P40, respectively (p < 0.05; Table 2).…”
Section: Chemical Analysissupporting
confidence: 62%
“…Ammonia is considered an intermediate or final product of the reactions of nitrogenous compounds released during the course of the Maillard reaction complex and Strecker degradation of amino acids [ 17 , 36 ]. Consistent with this statement, an increase in ammonia amount of 22 and 32% was observed as a result of the sterilisation process in P30 and P40, respectively ( p < 0.05; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation